Calendario 2026: La papa que da fuerza - International Potato Center (2025)
This illustrated calendar promotes the consumption of iron-biofortified potatoes as a strategy to improve nutrition and reduce anemia in Peruvian households. Through culturally relevant imagery and family-centered messages, the material highlights the nutritional value of potatoes and their role in healthy diets throughout the year. The calendar serves as an educational communication tool that links crop improvement, nutrition awareness, and food security, supporting CIP’s efforts to translate agricultural innovation into positive health outcomes.